Comparison of stents used for endovascular treatment of intracranial aneurysms. (2nd November 2018) - Mine, Benjamin; Bonnet, Thomas; Vazquez-Suarez, Juan Carlos; Iosif, Christina; Lubicz, Boris
ABSTRACT: Introduction : Stent-assisted coiling (SAC) has widened indications of endovascular treatment of intracranial aneurysms (wide-neck, fusiform aneurysms); moreover, it is associated with more stable anatomical results. Besides the development of other techniques such as flow diverter stents, bifurcation stents, or intrasaccular flow disruptors, SAC remains one of the most used endovascular techniques because it provides good clinical and anatomical results for most aneurysms. Several devices based on the same principle are available and have undergone many adaptations and developments over 20 years of intracranial stenting. Areas covered : The purpose of this article is to review and compare intrinsic properties of available devices and their anatomical and clinical performance. Expert commentary : Based on this review and our experience of SAC, we will discuss the behavior and performance of those devices in different anatomic and clinical situations.